2016
DOI: 10.1007/s11888-016-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtypes and Personalized Therapy in Metastatic Colorectal Cancer

Abstract: Development of colorectal cancer occurs via a number of key pathways, with the clinicopathological features of specific subgroups being driven by underlying molecular changes. Mutations in key genes within the network of signalling pathways have been identified; however, therapeutic strategies to target these aberrations remain limited. As understanding of the biology of colorectal cancer has improved, this has led to a move toward broader genomic testing, collaborative research and innovative, adaptive clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 83 publications
0
26
0
4
Order By: Relevance
“…However, the majority of patients with metastatic CRC (mCRC) experience a poor survival rate (3,4). A growing body of research has demonstrated the positive effect of molecularly targeted treatment on the survival rate of patients with mCRC, especially with the use of monoclonal antibodies against epidermal growth factor receptor (EGFR) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients with metastatic CRC (mCRC) experience a poor survival rate (3,4). A growing body of research has demonstrated the positive effect of molecularly targeted treatment on the survival rate of patients with mCRC, especially with the use of monoclonal antibodies against epidermal growth factor receptor (EGFR) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A CRC immunhisztokémiai és/vagy PCR-vizsgálata a mikroszatellita-instabilitás szűrésére gyakorlatban van a Lynch-szindróma kizárására [44]. Emellett a többi biomarkerrel kapcsolatban is születtek különböző eredmények, melyek részben még ellentmondásosak, és egyelőre nem alkalmazhatók megbízha-tóan a rutin klinikai gyakorlatban [45]. Az utóbbi idő-ben elfogadott, miszerint az MSI-fenotípusú II-III.…”
Section: Terápiaunclassified
“…Egy 2015-ben publikált adat szerint az MSI-H-daganatok jól reagáltak "programozott halál-1-es" immunellenőrzésipont-gátló (pembrolizumab-) terápiára az MSS-daganatokkal ellentétben [47]. További vizsgálatok folynak különféle immunellenőrzésipont-inhibitorokkal szemben is ebben a betegcsoportban [45]. A Schlicker és mtsai által leírt 1.2-es altípusú CRC (melyben MSI és lymphocytainfiltráció jellemző) magas érzékenységet mutatott továbbá a glikogén-szintáz-kináz, a c-Src és a Wnt-szignál inhibitoraival szemben [48].…”
Section: Terápiaunclassified
“…Due to the emergence of personalized medicine in cancer treatment, the need for biomarkers giving accurate and actual insight in the state of the disease is rising quickly [1]. In recent years, many new targeted drugs have come to the market for treating cancer patients, and a lot more are expected in the upcoming years [2,3]. Circulating biomarkers such as CTCs, circulating proteins, and nucleic acids are expected to contain the biomarkers needed to select a suitable therapy.…”
Section: Introductionmentioning
confidence: 99%